Průhled do způsobu života pražské měšťanské rodiny Měchurovy a Palackého kolem poloviny 19. století - Kořalka, Jiří (Lidé města, 2003)
The ethnographic study is based on a sample of 52 letters written since October 1826 by prominent Czech historian Frantíšek Palacký (1798-1876) to his bride Terezle Měchurová 1807-1860), after their marriage on Septemher 16, 1827 till her death on August 18, 1860. In the years of their common life, Palacký sent the letters to his wife mostly from far afield when as a historian and a member of the lmperial Academy of Sciences he resided in Vienna, Leipzig, Munich, Berlin, Dresden, Paris and on other places, or when as a member of the Austrian lmperial Diet he stayed in Vienna and Kroměříž from July 1848 till March 1849. An excellent observing ability and vividness transpire from Palacký's letters to Terezie from his four-month trip to Italy between mid-March and mid-July 1817. Vital information about the way of life is provided by summer letters from Prague, where Palacký pursued his academic career, while Terezie, mostly with both children, stayed at the castle in Otín, and later mainly in Lobkovice. They reflect the day-to-day worries about the summer changes in the house and flat as well as the arrangemenl of various affairs for the whole family with the Prague authorities, supply or drugs and various shopping in Prague. The Palacký family regularly made the most of the well-established, private nelwork of borrowed printed matters. Almost regularly, the flat was every week visited by a messenger who, for a small pay, offered and brought in person German books and literary magazines, in which the family showed interest. At a given time, he took them away and exchanged them for new titles. Year after year, before the heating season started and before Terezie returned to Prague, Palacký had to look after the preparation of stoves in all rooms, especially the complicated transport and subsequent felling of wood for heating. At that time, he also had to take up the difficult task of hiring new servants for the family for the winter period. The fact that Palacký wrote all letters to his bride and later wife Terezie in German bears witness of a far-reaching, supra-ethnic Czech-German symbiosis in Bohemia's capital until the large expansion of the Czech national movement in the 1860s. Almost all members of the large family of the big landowner Jan Měchura (1774-1852), into whose family Palacký married, only spoke German in both their verbal and written contacts. Their loyalty to the Austrian state did not clash with their Bohemian land patriotism. Their German education and culture were sometimes complemented in salons in conversations with aristocracy also with an effort at speaking French. Czech, basically understood by all, remained limited to the contact with servant and craftsmen, who sometimes worked in their home. Palacký spoke and wrote in German with his wife and most of her relatives, but after their son Jan (1830-1908) and daughter Marie (1833-1891) were born, he insisted on education and upbringing of his children in Czech and French. Since her early years, Terezie understood from her home simple Czech sentences, but she only learnt the Czech literary language in the last decade of her life, after 1850. Since his childhood, all of Palacký's life was accompanied with an unusual feeling of responsibility. He observed in a strict and economical manner the timetable of his working day he had set for himself. His regular habits and admirable self-discipline were among the elementary conditions of a successful fulfilment of his basic, life-long mission. He had a wonderful, regular and quite easily readable handwriting, which had found many admirers both in his time and later. Palacký used fine Roman letters to write all of his German texts and letters. ln the relationship to the ill Terezie, an outstanding role was played by Palacký's deeply established consciousness of Christian duty. He realised that through his selfless care and love he could protect Terezie against bad people and contribute to the improvement of her health condition. Since his marriage with Terezie, the private life of František Palacký mainly took place in the large family of Jan Měchura. The family circle was dominated without any restrictions by Palacký's father-in-law, who tried to keep a decisive influence also on the life of his married daughters. By contrast, his son Leopold Měchura (1804-1870), a big landowner and composer, managed to escape the immediate reach of his father's grip after a marriage which was postponed several times. Jan Měchura was a rich, but very thrifty man. According to unwritten rules of large middle-class families, he paid his married, older daughter Terezie a regular quarterly contribution of 120 to 150 florins for more than two decades after her marriage till his death. A similar allowance was paid from her father to his younger daughter Antonie (1809-1836), who married forester Jan Heyrovský (1800-1865) in June 1832, but she died in January 1836. On the basis of this, Jan Měchura appropriated himself the right to intervene in the education and place of residence of his granddaughter Leopoldina. Hence his sharp clashes with his son-in-law in the affair. Palacký's letters to Terezie also reveal that a minor allowance, roughly ten florins a month, were paid to the poor relative Brigitte Keybl (1788-1865), the younger sister of Jan Měchura's late first wife. The large family never wanted to admit that any, even quite a distant, relative had to face poverty. Unlike most contemporary national activists, Palacký did not have to provlde immediate subsitence to his wife and the whole family; this was ensured by his father-in-law Jan Měchura. Personal money of Palacký and his wife were strictly separated. But this did not prevent Palacký from financially supporting his relatives in eastern Moravia, although sometimes he had to borrow the money. Palacký´s letters to Terezie confirm the information that original private letters, not destined for the public, provide a much more reliable account of the impulses to the thought and deeds of great historical personalities, if they are compared with later assessments, recollections and attempts at justification ex post.